2014
DOI: 10.1016/j.pain.2013.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, surgical, and sociodemographic predictors of pain outcomes after breast cancer surgery: A population-based cohort study

Abstract: On behalf of the Recovery Study Group. Psychological, surgical and sociodemographic predictors of pain outcomes after breast cancer surgery: a population-based cohort study, PAIN (2013), doi: http://dx.doi.org/10. 1016/j.pain.2013.09.028 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
190
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(214 citation statements)
references
References 49 publications
15
190
5
4
Order By: Relevance
“…The finding that predictive power did not differ across thresholds for defining persistent pain was strengthened by 2 cohort studies that used separate regression models for both high and low thresholds of persistent pain and reported similar associations across predictors. 26,35 Whether or not we incorporated missing data for nonsignificant predictors or converted categorical data for age and BMI to continuous data (Appendix 13, available at www.cmaj.ca/lookup/suppl/ doi:10.1503/cmaj.151276/-/DC1) did not appreciably influence the results. 42 Wilson et al, 2013 49 Mejdahl et al, 2013 26 Johansen et al, 2014 52 Lundstedt et al, 2012 41 De Oliveira et al, 2014 37 Steegers et al, 2008 44 Meretoja et al, 2014 58 Yang et al, 2010 51 Tasmuth et al, 1997 46 Shahbazi et al, 2015 60 Husen et al, 2006 40 Bell et al, 2014 59 Swenson et al …”
Section: Subgroup Analyses Meta-regression and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that predictive power did not differ across thresholds for defining persistent pain was strengthened by 2 cohort studies that used separate regression models for both high and low thresholds of persistent pain and reported similar associations across predictors. 26,35 Whether or not we incorporated missing data for nonsignificant predictors or converted categorical data for age and BMI to continuous data (Appendix 13, available at www.cmaj.ca/lookup/suppl/ doi:10.1503/cmaj.151276/-/DC1) did not appreciably influence the results. 42 Wilson et al, 2013 49 Mejdahl et al, 2013 26 Johansen et al, 2014 52 Lundstedt et al, 2012 41 De Oliveira et al, 2014 37 Steegers et al, 2008 44 Meretoja et al, 2014 58 Yang et al, 2010 51 Tasmuth et al, 1997 46 Shahbazi et al, 2015 60 Husen et al, 2006 40 Bell et al, 2014 59 Swenson et al …”
Section: Subgroup Analyses Meta-regression and Sensitivity Analysesmentioning
confidence: 99%
“…36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Persistent post-surgical pain lasting over 3 months is a common complication following breast surgery [162], with a reported incidence between 20% and 68% [163][164][165][166]. The variance may be attributed to multiple factors, including differences in definition and the type of breast cancer surgery treatment involved.…”
Section: Persistent Post-surgical (Chronic) Painmentioning
confidence: 99%
“…12 Several studies have indicated that psychological comorbidity is a risk factor for PPBCT, 1,13 with recent prospective studies indicating a correlation between preoperative psychological symptoms and PPBCT. 3,4,14,15 A prevalence of preoperative depression of 37% and anxiety of 70% has been reported among patients with breast cancer, 16 whereas the prevalence of severe psychological distress has been reported to be around 40%. [17][18][19] Longitudinal studies suggest a reciprocal relationship between depression and pain, 20,21 in that depression may lead to pain and vice versa.…”
Section: Introductionmentioning
confidence: 99%